Relationship between Drug Craving and HighRisk Situations for Relapse Among Inmates with Substance Abuse Issues - Nurulatiqah, Yunos; Fauziah, Ibrahim; Ezarina, Zakaria; Wan Shahrazad, Wan Sulaiman; Nazirah, Hassan; Mohammad Rahim, Kamaluddin; Tharshini, N. K. (IJCRR, 2021)
Introduction: Relapse occurs when there is a strong desire for repeating drug-seeking behaviour due to high-risk situations such as social environment, interpersonal conflict, and negative emotions. Objective: This article aims to analyse the relationship between drug craving and high-risk situations for relapse among inmates with substance abuse issues serving in Malaysian prisons. Material and Methods: This study was conducted using a quantitative approach. A total number of 407 inmates with substance abuse issues were randomly selected as respondents of the study. The data were analysed using descriptive and inferential analysis via SPSS software. Results: The result indicates that there is a positive and significant moderate relationship between drug craving and high-risk situations for relapse (r=0.452, p˂0.01). Therefore, it can be concluded that drug craving is associated with high-risk situations for relapse among inmates with substance abuse issues. Conclusion: The findings of this study is expected to provide implications to the stakeholders such as counsellors and drug rehabilitation officers to improvise the existing rehabilitation modules and programs to address relapse issues among inmates in Malaysia.